Konflik Moral dan Rasa Bersalah Tokoh Kakek Cerpen “Robohnya Surau Kami” Perspektif Psikoanalisis Sigmund Freud - Ayu Ida Maulida; Aida Awwalina Nurussyifa; Resdianto Permata Raharjo; Indah Puspitasri (Universitas Palangka Raya, 2026)
This study discusses the moral conflict and guilt experienced by the Grandfather character in the short story “Robohnya Surau Kami” by A.A. Navis through Sigmund Freud’s psychoanalytic perspective. The study aims to describe the forms of moral conflict, guilt, and the dynamics of id, ego, and superego that influence the psychological condition of the character. This research employed a qualitative descriptive method with a literary psychology approach. The data source was the short story “Robohnya Surau Kami”, while the data consisted of narrative quotations, dialogues, and expressions indicating psychological conflict experienced by the character. Data collection techniques were conducted through reading and note-taking methods, followed by data analysis using Freud’s psychoanalytic theory. The findings reveal that the Grandfather character experiences deep moral conflict after realizing that the worship he devoted throughout his life is considered meaningless because it ignores social responsibility. The dominance of the superego causes excessive guilt, anxiety, self-punishment, and psychological pressure that eventually lead to self-destructive behavior. The imbalance between id, ego, and superego also strengthens the character’s inner conflict. This study implies that literary works can represent complex human psychological conditions and demonstrates the relevance of Freud’s psychoanalytic theory in analyzing Indonesian literary works, particularly in understanding moral conflict and guilt experienced by literary characters.